PATRIARKI DAN KESETARAAN GENDER DALAM TAFSIR KLASIK DAN KONTEMPORER - SHOKHIBUL MIGHFAR; MELATI PUTRI, ANDITA MARSELA; BADARUDIN MUHAMMAD KHADAM (Jurnal Payung Sekaki : Kajian Keislaman, 2024)
The purpose of this paper is to determine patriarchy and gender equality in classical and contemporary interpretations. This research is a library research. Primary data is obtained from classical and contemporary interpretations. The data collection technique used is the documentation technique. Furthermore, the collected data is grouped and arranged systematically, and analyzed critically using deductive and inductive methods. So that the results of this study can produce accurate and accountable conclusions. The results of the study indicate that patriarchy is a term that places men above women both in the family and society. While gender equality is a view that equates men and women to obtain opportunities and rights and obligations as human beings. The concept of gender emphasizes more on the aspects of masculinity or femininity of a person. There are several verses of the Quran concerning the equality of